Telegram from Max Bredig to Otto Schray, April 4, 1941 - Bredig, Max Albert (1941)
Max Bredig (1902-1977) tells Otto Schray that tickets for Marianne Homburger (1903-1986), Paul Homburger (1882-1965), and Viktor Homburger (1888-1968) have been booked from Lisbon.
Keywords: Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Jewish Holocaust (1939-1945); Emigration and immigration; Homburger, Paul Philipp, 1882-1965; World War (1939-1945)